Tranquility-Calmness Parenting of Modern Stoicism - Pertiwi, Yacintha; Marhayati, Nelly (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Parental anxiety increased during the covid 19 pandemic in 2019, many parents had to go more extra to look after and care for their children at home. Parents become irrational in thinking, their emotions become unstable which results in miscommunication and misunderstanding with children. Thus this research aims to uncover concepts and applications of parenting from the perspective of modern-era stoicism that can answer the problem of anxiety in parents today in realizing calm and happiness. ThroughÂ  Research Library and methods Content Analysis the author uses a cognitive psychology approach and a philosophical approach model on actual problems. The results of study include an explanation of application of parenting from the perspective of modern-era stoicism, which are self-control and emotion, focus on what is controlled, trichotomy of control, educating children with calm wisdom and being grateful, foster children's social relations, understand about loss or death, and find peace of self.